A dinâmica de inovação tecnológica na agroindústria no Rio Grande do Sul: um caso comparativo entre a produção e o beneficiamento de arroz e de soja - Batista, Eduardo Roberto Soares (Universidade do Vale do Rio dos Sinos, 2020)
Technological innovation is present in different stages of the agribusiness value chain. The growth of grain production in the State of Rio Grande do Sul in recent decades has stimulated the demand and the launch of new products that meet the growing need for more productivity and profitability. The main objective of this work is to analyse the innovations that have occurred in the equipments related to the processing of rice and soybeans in the last 50 years, comparing the dynamic of innovations in the processing analysis unit with that of grain production. The research method is based on documentary research and interviews. Documentary research provided, through the adoption of the historical method, a view on the sequence of innovations incorporated in the production and processing of rice and soybeans. The interviews with actors in the grain production chain (producers and equipment manufacturers) identified how innovations occurred in this chain, highlighting the implementation mechanisms, the motivating aspects and the restrictions on the adoption of innovations. The results suggest that the dynamism of technological innovation in grain processing equipments was less than that related to grain production. The theoretical contribution of this thesis is to show what were these aspects and the reasons why they were more prevalente in one unit of analysis than in the other. The research showed that the basis on which companies compete, how innovations are dependent on each other, and the need for joint action by companies to present a solution to the producer were key factors in encouraging technological innovations. In the grain production analysis unit, competition based more on technology than on the price, with the presence of some disruptive innovations, encouraged the improvement of equipaments. In grain production, the greater dependence on input or equipament innovation has resulted in a boost of associated innovations from different companies. The need for joint actions between companies in the production unit to propose more complete solutions for producers encouraged the approximation between the companies. These factors were less relevant in the grain processing unit’s innovation dynamic. In this analysis unit there were a predominance of incremental, individualized and reactive innovations in response to the increase in productivity resulting from the innovation in production.
Keywords: Dinâmica de inovação; Tecnologia agrícola; Beneficiamento de arroz; Beneficiamento de soja; Innovation dynamic; Agricultural technology; Rice processing; Soybean processing; ACCNPQ::Engenharias::Engenharia de Produção